1980
DOI: 10.1056/nejm198003273021301
|View full text |Cite
|
Sign up to set email alerts
|

Successful Bone-Marrow Transplantation for Infantile Malignant Osteopetrosis

Abstract: A five-month-old girl with autosomal-recessive osteopetrosis received a bone-marrow transplant from her five-year-old HLA-MLC-identical brother after preparation with cyclophosphamide and modified total-body irradiation. Engraftment was documented by chromosomal analysis. Anemia, thrombocytopenia, and leukoerythroblastosis corrected within 12 weeks of transplantation. Low serum calcium and elevated serum alkaline and acid phosphatase levels became normal. Serial x-ray studies revealed bony remodeling and new n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
134
0
8

Year Published

1983
1983
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 427 publications
(146 citation statements)
references
References 33 publications
4
134
0
8
Order By: Relevance
“…5 Since 1977, allogeneic haematopoietic stem cell transplantation (HSCT) had been successfully applied in single cases and small groups of AR-OP patients. [6][7][8][9] In 1994, our group reported the results in 69 patients, showing a favourable outcome of HSCT with a (genotype) HLA-identical donor. 10 Treatments with approaches other than HSCT such as corticosteroids, high doses of calcitriol (vitamin D 3 ) and interferon-g, have been disappointing.…”
mentioning
confidence: 98%
“…5 Since 1977, allogeneic haematopoietic stem cell transplantation (HSCT) had been successfully applied in single cases and small groups of AR-OP patients. [6][7][8][9] In 1994, our group reported the results in 69 patients, showing a favourable outcome of HSCT with a (genotype) HLA-identical donor. 10 Treatments with approaches other than HSCT such as corticosteroids, high doses of calcitriol (vitamin D 3 ) and interferon-g, have been disappointing.…”
mentioning
confidence: 98%
“…Early studies had demonstrated that OCPs originate from the haematopoietic stem cells (Sheven et al, 1986;Hagenaars et al, 1989;Hattersley & Chambers, 1989;Kurihara et al, 1989;Matayoshi et al, 1996) and circulate in PB (Walker, 1973(Walker, , 1975Kahn & Simmons, 1975;Coccia et al, 1980;Faust et al, 1999;. However, whether OCPs possess surface characteristics that distinguish them from other PBMCs (in particular monocytes) is not known.…”
mentioning
confidence: 99%
“…On the other hand, many in vivo studies in animals as well as in man have shown that mononuclear osteoclast precursors may be disseminated through the body via the blood vascular system (5)(6)(7)(8)(9). This has led several investigators to study the capacity of blood monocytes or tissue macrophages to resorb bone mineral by co-culturing them with devitalized bone tissue or particles of dried, ground bone (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%